# Prove that: (1+\frac{1}{\tan^2A})(1+\frac{1}{\cot^2A})=\frac{1}{\sin^2A

Prove that:
$\left(1+\frac{1}{{\mathrm{tan}}^{2}A}\right)\left(1+\frac{1}{{\mathrm{cot}}^{2}A}\right)=\frac{1}{{\mathrm{sin}}^{2}A-{\mathrm{sin}}^{4}A}$
You can still ask an expert for help

## Want to know more about Trigonometry?

• Questions are typically answered in as fast as 30 minutes

Solve your problem for the price of one coffee

• Math expert for every subject
• Pay only if we can solve it

Clara Reese
We use the basic trigonometry formula to solve the equation.
Prove: $\left(1+\frac{1}{{\mathrm{tan}}^{2}A}\right)\left(1+\frac{1}{{\mathrm{cot}}^{2}A}\right)=\frac{1}{{\mathrm{sin}}^{2}A-{\mathrm{sin}}^{4}A}$
$L.H.S.=\left(1+\frac{1}{{\mathrm{tan}}^{2}A}\right)\left(1+\frac{1}{{\mathrm{cot}}^{2}A}\right)$
$=\left(\frac{{\mathrm{tan}}^{2}A+1}{{\mathrm{tan}}^{2}A}\right)\left(\frac{{\mathrm{cot}}^{2}A+1}{{\mathrm{cot}}^{2}A}\right)$
$=\left(\frac{{\mathrm{sec}}^{2}A}{{\mathrm{tan}}^{2}A}\right)\left(\frac{{\mathrm{csc}}^{2}A}{{\mathrm{cot}}^{2}A}\right)$
$=\left(\frac{\frac{1}{{\mathrm{cos}}^{2}A}}{\frac{{\mathrm{sin}}^{2}A}{{\mathrm{cos}}^{2}A}}\right)\left(\frac{\frac{1}{{\mathrm{sin}}^{2}A}}{\frac{{\mathrm{cos}}^{2}A}{{\mathrm{sin}}^{2}A}}\right)$
$=\left(\frac{1}{{\mathrm{sin}}^{2}A}\right)\left(\frac{1}{{\mathrm{cos}}^{2}A}\right)$
$=\left(\frac{1}{{\mathrm{sin}}^{2}A}\right)\left(\frac{1}{1-{\mathrm{sin}}^{2}A}\right)$
$=\frac{1}{{\mathrm{sin}}^{2}A-{\mathrm{sin}}^{4}A}$
L.H.S=R.H.S
Hence prove.